Use of the Chatbot as a virtual assistant in learning platforms - Martin Vallejos, Nicolas; De La Cruz Gaviria, Diego Edgar; Alarcon, Felipe (LACCEI, 2024)
As part of the research objective, the importance of the use of the chatbot in learning platforms by students is made known, with the purpose of generating interest and motivation in their academic stage, so that they generate self-training without depending on of the human; Likewise, it will serve to improve your academic performance. Method: Applying the Prisma method, 508 articles were identified from the Scopus and IEEE databases, where 25 studies were recovered in the inclusion and exclusion criteria. On the other hand, the analysis of these 25 studies generated a broad comparison from factors such as information obtaining techniques, architecture, tools and methods. Results: 5 architectures were identified in the articles analyzed, where one of the most used was “Vosviewer”, with 33.33% of the total articles reviewed. Finally, in the studies examined above, 4 implemented tools were identified where the most used tools were programming languages, including HTML, JS, PHP and NODE.JS, the latter 2 for communication with servers; all this representing 44%. It can be shown that one of the most recurrent sample sizes in the studies were universities, all of which represented 47%. Finally, 4 instruments were identified where chatbots were implemented. It is observed that the most used was web systems with 33%; since, these were used because the same chatbotsConclusions: The variation of data sets, the development of more specific tools, architectures and methods and the detection of collaboration approaches between teams are presented as the key points to provide greater depth in the field of advanced technology and maximize the positive impact of chatbots on virtual platforms, so researchers are encouraged to carry out more studies focused on education in the country through this tool.